Sulfur dioxide adsorption by iron oxide nanoparticles@clinoptilolite/HCl - Mina Mahmoodi Meimand; Ahmad Jonidi Jafari; Alireza Nasiri; Mohammad Malakootian (Journal of Air Pollution and Health, 2020)
Introduction: The purpose of this study was to investigate and compare the effect of iron oxide nanoparticles on the adsorption of sulfur dioxide by modified zeolite with hydrochloric acid. In this investigation was used modified zeolite with HCl with and without iron oxide nanoparticles (Iron Oxide Nanoparticles@Clinoptilolite/HCl) as adsorbent. Materials and methods: Structural characteristics, chemical composition and specific surface area of adsorbent were determined using the FTIR, FESEM, EDX, Mapping, XRD, XRF and BET techniques. Glass cylinder filled with zeolite seeds and SO2 cylinder balanced with N2 gas was used for experiments. It was evaluated factors affecting SO2 uptake process including temperature and contact time, also thermodynamics and kinetics of adsorption. Sulfur dioxide adsorption of real sample was taken with both adsorbents. Results: Adsorption efficiency of SO2 in the synthetic and actual sample were %82.8±5.5 and %67.2±7.21 respectively, by modified zeolite with HCl and iron oxide nanoparticles in the optimum conditions of temperature of 25 °C and duration 28.5 min. As well as, removal percentage average was obtained in the synthetic and actual sample %46.1±4.34 and %35.8±5.85 respectively, by modified zeolite with HCl without nanoparticles in optimum condition of temperature of 25 °C and contact time of 20.5 min.The results showed that SO2 adsorption is an exothermic and spontaneous process and adsorption kinetics of sulfur dioxide by both adsorbent is more consistent Pseudo-second order kinetics model. Conclusion: The use of iron oxide nanoparticles on the zeolite can increase SO2 removal efficiency from the gas phase.